PENGEMBANGAN SEKTOR UTAMA REGIONAL PENDEKATAN EFISIENSI TEKNIKAL DAN SIKLUS BISNIS Studi Kasus di Propinsi Bali - Awirya, Agni Alam (Universitas Negeri Semarang, 2011)
The appropriate resource allocation on potential economic sectors can spur a faster economic growth. Knowledge on economic sectors which are efficient and have experiencing positive business cycle could ease the allocation of available economic resources. This research provides information on the technical efficiency of economic sectors as well as the business cycle of the economy inÂ Bali. A stochastic frontier method is used to analyze the technical efficiency of economic sectors while the Bry-Boschan algorithm is used to estimate the business cycle of the economic sectors which are relatively efficient. The estimation result indicates that the efficient economic sectors in Bali are trade, hotel & restaurant (thr) sector and agriculture sector. Both sectors contribute most on the Baliâ€™s economic output. At the end of the observation period, the economic business cycle in Bali is in a period of contraction. It is estimated that the next quarter will be the expansion period.